Efficacy of models as teaching tools for the measuring and estimating of pad foundation excavation / An Nisha Nur Welliana Abd Rased ... [et al.] - Abd Rased, An Nisha Nur Welliana; Samsul Rijal, Nurhidayah; Zulkernain, Muhammad Zahir; Mohd Hashim, Mohamad Haszirul (Universiti Teknologi MARA, Kedah, 2023)
Excavation pad foundation in subject measuring and estimating is an important part of any civil engineering course that is necessary to calculate the dimensions and volume. However, conventional approaches of teaching this topic that rely solely on theoretical frameworks and classroom lectures may not effectively translate to real-world applications. Lack of practical knowledge and visual depiction of the excavation pad foundation may result in misconceptions, inaccurate measurement, and unsafe estimating practices in actual projects. The employment of models as teaching tools for this topic in measuring and estimating may provide a solution to these problems. Therefore, this study’s objective is to investigate the effectiveness of using models as aids in teaching subject measurement and estimating for the excavation of pad foundation topic. To clearly represent the model parts, the pad foundation is likewise made of colored polystyrene, and the reinforcing frame is built of wire. The data from the questionnaire regarding the students' perceptions of learning outcomes before and after the model’s application were analyzed. From this model, students can gain a deeper comprehension of the concepts involved in excavation pad foundation by using models, which can lead to more accurate and efficient construction practices. Moreover, this approach has significant commercialization potential. The models may be used in civil engineering and construction worker/contractor training programs to teach excavation pad foundations in measuring and estimating. This requires innovative educational resources, including model kits, computer programs, and instructional videos.